Modeling sulfide production in full flow concrete sewers based on the HRT variation of sewerage - Junyan Wang (IWA Publishing, 2021)
The corrosion and odor in concrete sewers are mainly related to the sulfide production, which is, under certain circumstances, directly proportional to the hydraulic retention time (HRT) of the sewer. To reduce the corrosion and control the odor in concrete sewers, it is necessary to model the production of sulfide in the concrete sewers with different HRTs. However, previous researches were mostly carried out in simulated Perspex-made sewers, and the obtained theoretical formulas based on the Monod equation were impractical because of the complexity. An actual concrete pipe with domestic sewage was employed in this study to obtain a simple but practical model, which can be applied to quantitively describe the sulfide production according to the HRT of the sewer and the chemical oxygen demand (COD) of the sewage. The empirical equation obtained was , the coefficient is a logarithmic function of the HRT, and the sulfide production rate and COD have a power relationship. Based on the data of COD and HRT obtained in the realistic sewer, the production of sulfide in the sewer can be predicted for better maintaining sewers through sulfide control. HIGHLIGHTS An actual concrete pipe was used to evaluate the effect of HRT on the variation of pollutants.; Few degradations of nitrogen and phosphorus in an actual concrete pipe were found with HRT.; The degradation of COD in an actual concrete pipe accorded with the first-order reaction law.; Sulfide production rate was the power function of solute COD, and the coefficient is the logarithmic function of the HRT.;